Nutritional Status Eating Habits and Cardiovascular Risk in Volunteer Firefighters of Paraguay - Ochoa Ferreira, Nayeli Monserrath; Cáceres Zaracho, Nathalia Jazmín; Benítez Desvars, Alicia Viviana; López Ocampos, María Isabel; Aveiro Róbalo, Telmo Raul (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Introduction: cardiovascular diseases are the leading causes of mortality and morbidity worldwide, this could be reduced by a change in lifestyle. In firefighter activities increase the risk of sudden cardiac events.Objective: to determine the cardiovascular risk according to the Framingham scale, dietary habits and nutritional status of volunteer firefighters in Capital in the period between June and September 2023.Materials and Methods: quantitative, descriptive, observational, cross-sectional, cross-sectional study based on a questionnaire with open-ended questions about dietary habits and a Framingham study that assesses cardiovascular risk at 10 years by means of scores.Results: of the 100 % of those surveyed, only 24,29 % had an adequate nutritional status according to BMI and 75,71 % presented malnutrition due to excess (overweight and obesity), while poor eating habits and excessive consumption of sugary drinks were observed; most of the sample presented a low cardiovascular risk according to the Framingham Heart Study calculator.Conclusion: most of the firefighters evaluated presented excess body weight, which leads to a negative relationship between eating habits and nutritional status and may present a risk of heart disease.